2020
DOI: 10.1002/anie.202006212
|View full text |Cite
|
Sign up to set email alerts
|

A Multitarget Gold(I) Complex Induces Cytotoxicity Related to Aneuploidy in HCT‐116 Colorectal Carcinoma Cells

Abstract: A novel alkynyl phosphane gold(I) complex (trimethylphosphane)(3‐(1,3‐dimethylxanthine‐7‐yl)prop‐1‐yn‐1‐yl)gold(I) 1 displayed mutiple biological activites including selective proliferation inhibitory, anti‐metastatic, and anti‐angiogenic effects. The complex also induced effects related to aneuploidy in HCT‐116 colon carcinoma cells, which might be mainly ascribed to the dysfunction of mitochondrial bioenergetics and downregulation of glycolysis. Induction of aneuploidy beyond a critical level can provide an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…We hypothesize that an ideal combination of hydrophilic/lipophilic character and reduced metallodrug speciation due to the high stability of the Au−C bonds may be responsible for the overall observed effects of 3 in the parasite. Noteworthy, caffeine‐based metal complexes have already shown promising pharmacological properties as anticancer and antimicrobial agents [36,37,38] …”
Section: Figurementioning
confidence: 99%
“…We hypothesize that an ideal combination of hydrophilic/lipophilic character and reduced metallodrug speciation due to the high stability of the Au−C bonds may be responsible for the overall observed effects of 3 in the parasite. Noteworthy, caffeine‐based metal complexes have already shown promising pharmacological properties as anticancer and antimicrobial agents [36,37,38] …”
Section: Figurementioning
confidence: 99%
“…The Casini group applied purine‐based NHC ligands for G‐quadruplex interactions [12] . The Ott group described the multivalency of potential targets of xanthine‐derived alkynylgold(I) complexes, including aneuploidy induction for cancer cell death, anti‐metastatic and vascular disruption effects [13] . Enhancement of oxidative stress induction has been explored by the same group using NHC ligands equipped with ferrocenyl moieties and also by Wei and co‐workers by decorating the ligand with a naphthoquinone motif with subsequent promotion of immunogenic cell death [14] .…”
Section: Figurementioning
confidence: 99%
“…[12] The Ott group described the multivalency of potential targets of xanthine-derived alkynylgold(I) complexes, including aneuploidy induction for cancer cell death, anti-metastatic and vascular disruption effects. [13] Enhancement of oxidative stress induction has been explored by the same group using NHC ligands equipped with ferrocenyl moieties and also by Wei and coworkers by decorating the ligand with a naphthoquinone motif with subsequent promotion of immunogenic cell death. [14] According to this latter work, the redox imbalance experienced by the treated cells triggered an effective anticancer immune response through the generation of death signals known as damage-associated molecular patterns (DAMPs).…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] Recently a few [Au(I)(alkynyl) (phosphane)] complexes have been reported that showed promising in vitro and in vivo activities, although their number has remained small compared to other gold complexes. [19][20][21][22][23] Here we report alkynyl phosphane and alkynyl NHC Au(I) complexes where the alkynyl ligand is a derivative of the quinazoline carboxamide class of ligands that bind to the translocator protein 18 kDa (TSPO). TSPO is a relatively small transmembrane protein on the outer mitochondrial membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Different classes of Au complexes have been evaluated to date; (i) neutral linear auranofin‐type phosphane complexes, (ii) tetrahedral cationic Au(I) phosphane complexes, usually containing chelating bis(phosphane) ligands, (iii) linear Au(I) N ‐heterocyclic carbene (NHC) complexes and (iv) square‐planar Au(III) complexes [9–18] . Recently a few [Au(I)(alkynyl) (phosphane)] complexes have been reported that showed promising in vitro and in vivo activities, although their number has remained small compared to other gold complexes [19–23] …”
Section: Introductionmentioning
confidence: 99%